The Retrospective Analysis of Unemployment in the Conditions of Transformational Shifts in the Labor Market of Ukraine - Naumova Maryna A. (Bìznes Inform, 2018)
The article is aimed at analyzing the unemployment in Ukraine over the years of its formation as an independent State, determining its main tendencies, and developing priority measures that can help to eliminate the negative impact of unemployment on the labor market. A retrospective analysis of unemployment in Ukraine was carried out in the context of gender segregation, age groups, degrees of education, professional-qualification structure, duration of unemployment, reasons of unemployment, types of economic activities. The main reasons and factors influencing its dynamics were studied. The negative consequences of unemployment together with some positive externalities have been allocated. The author considers dynamics of the unemployment rate, registered unemployment, the ratio of the total number of unemployed population of Ukraine and the population, which become accounted by the State employment service. A detailed analysis of the labor market development in the coordinates of the unemployment rate and vacancy norme using the Beveridge curve was carried out and five stages of its transformations have been allocated. The priority directions of development which can facilitate an improvement of the situation on the labor market and the transition to productive and innovative employment are provided.